Evaluation models of some morphological characteristics for talent scouting in sport - Rogulj, N.; Papic, V. L.; Cavala, M. (Collegium Antropologicum, 2009)
In this paper, for the purpose of expert system evaluation within the scientific project »Talent scouting in sport«, two methodological approaches for recognizing an athlete`s morphological compatibility for various sports has been presented, evaluated and compared. First approach is based on the fuzzy logic and expert opinion about compatibility of proposed hypothetical morphological models for 14 different sports which are part of the expert system. Second approach is based on determining the differences between morphological characteristics of a tested individual and top athlete`s morphological characteristics for particular sport. Logical and mathematical bases of both methodological approaches have been explained in detail. High prognostic efficiency in recognition of individual`s sport has been determined. Some improvements in further development of both methods have been proposed. Results of the research so far suggest that this or similar approaches can be successfully used for detection of individual`s morphological compatibility for different sports. Also, it is expected to be useful in the selection of young talents for particular sport.